(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2018)
This article contains a description of marketing actions that are undertaken by TSL companies. The purpose of the article was an analysis of marketing instruments on the market of logistics services in Poland and in Ukraine. A literature analysis and a comparative analysis were performed in relation to the services offered. The logistics services market in Poland was presented and compared to the Ukrainian market. A presentation was provided of those marketing elements that are realized in Poland and in Ukraine by selected logistics operators and of the instruments that are formed by them in both countries. Attention was paid in the article to the development trends of logistics services and the dynamics of changes in selected logistics companies.